Risk Factors Associated with the Development of Hospital-Acquired Infections in Hospitalized Patients with Severe COVID-19 - Fernando Solís-Huerta; Bernardo Alfonso Martinez-Guerra; Carla Marina Roman-Montes; Karla Maria Tamez-Torres; Sandra Rajme-Lopez; Narciso Ortíz-Conchi; Norma Irene López-García; Guadalupe Yvonne Villalobos-Zapata; Andrea Rangel-Cordero; Janet Santiago-Cruz; Luis Fernando Xancal-Salvador; Steven Méndez-Ramos; et al. (MDPI AG, 2023)
Recognition of risk factors for hospital-acquired infections (HAI) in patients with COVID-19 is warranted. We aimed to describe factors associated with the development of HAI in patients with severe COVID-19. We conducted a retrospective cohort study including all adult patients admitted with severe COVID-19 between March 2020 and November 2020. The primary outcome was HAI development. Bivariate and multiple logistic regression models were constructed. Among 1540 patients, HAI occurred in 221 (14%). A total of 299 episodes of HAI were registered. The most common HAI were hospital-acquired/ventilation-associated pneumonia (173 episodes) and primary bloodstream infection (66 episodes). Death occurred in 387 (35%) patients and was more frequent in patients with HAI (38% vs. 23%, p < 0.01). Early mechanical ventilation (aOR 18.78, 95% CI 12.56-28.07), chronic kidney disease (aOR 3.41, 95% CI 1.4-8.27), use of corticosteroids (aOR 2.95, 95% CI 1.92-4.53) and tocilizumab (aOR 2.68, 95% CI 1.38-5.22), age ≥ 60 years (aOR 1.91, 95% CI 1.27-2.88), male sex (aOR 1.52, 95% CI 1.03-2.24), and obesity (aOR 1.49, 95% CI 1.03-2.15) were associated with HAI. In patients with severe COVID-19, mechanical ventilation within the first 24 h upon admission, chronic kidney disease, use of corticosteroids, use of tocilizumab, age ≥ 60 years, male sex, and obesity were associated with a higher risk of HAI.